1997
DOI: 10.1108/08876049710158330
|View full text |Cite
|
Sign up to set email alerts
|

Service guarantees and consumers’ evaluation of services

Abstract: Realization of the long-term goals of any organization ultimately must revolve around customer satisfaction. This is particularly true in restaurants, where failure to satisfy customers will quickly lead to an early termination of the business. General levels of consumer dissatisfaction with service quality at restaurants are very high -in 1995 over 50 percent of restaurant patrons surveyed cited no aspect of service as being excellent. This finding is consistent with the high levels of failure among restauran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 5 publications
(6 reference statements)
0
43
0
Order By: Relevance
“…Thus, unlike previous studies that have treated service guarantees as explicit operation strategies or activities used to credibly signal high quality to customers (Tucci and Talaga, 1997) and studies that have mainly focused on such guarantees' direct effect in promoting service offerings (McDougall et al, 1998;Hays and Hill, 2001;Marmorstein et al, 2001), this paper aims to explore the role of perceived service The effect of service convenience guarantee strength as an implicit moderating variable in the relationship between service convenience and customer satisfaction. In other words, this paper treats service guarantee strength as implicit and perceived by customers no matter whether there is an explicit service guarantee expressed (Hays and Hill, 2006).…”
Section: Introductionmentioning
confidence: 87%
“…Thus, unlike previous studies that have treated service guarantees as explicit operation strategies or activities used to credibly signal high quality to customers (Tucci and Talaga, 1997) and studies that have mainly focused on such guarantees' direct effect in promoting service offerings (McDougall et al, 1998;Hays and Hill, 2001;Marmorstein et al, 2001), this paper aims to explore the role of perceived service The effect of service convenience guarantee strength as an implicit moderating variable in the relationship between service convenience and customer satisfaction. In other words, this paper treats service guarantee strength as implicit and perceived by customers no matter whether there is an explicit service guarantee expressed (Hays and Hill, 2006).…”
Section: Introductionmentioning
confidence: 87%
“…A11'examination of existing service showed that they are a multidimensional construct and not unidimensional as previously suggested (Tucci & Talaga, 1997). Specifically, guarantees can var; with respect to two main aspects.…”
Section: Methodsology Pretest and Manipulation Of Service Attributesmentioning
confidence: 75%
“…They are considered an important and effective means of presenting clear standards for consumers, supporting service development, signalling quality, increasing quality perception, reducing perceived risk, decreasing the perceived likelihood of service failure, attracting and retaining customers, enhancing customer satisfaction, increasing purchase intentions, encouraging positive word-of-mouth recommendations, and gaining market share through differentiation (Boulding & Kirmani, 1993;Evans, Clark, & Knutson, 1996;Hart, 1988;Hart et al, 1992;Hill, Hays, & Naveh, 2000;Kashyap, 2001;Kirmani & Rao, 2000;Lidén & Sandén, 2004;McDougall et al, 1998;Ostrom & Iacobucci, 1998;Tucci & Talaga, 1997;Wirtz & Kum, 2001;Wirtz et al, 2000). Numerous studies also have demonstrated that the provision of a service guarantee improves the expected service quality, reduces perceived risk, and increases the willingness to buy (Boshoff, 2003;Ostrom & Iacobucci, 1998;Wirtz et al, 2000).…”
Section: The Service Industries Journalmentioning
confidence: 97%